2016
DOI: 10.1016/j.bone.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Aging alters bone-fat reciprocity by shifting in vivo mesenchymal precursor cell fate towards an adipogenic lineage

Abstract: Bone marrow derived mesenchymal progenitor cells (MPCs) play an important role in bone homeostasis. Age-related changes occur in bone resulting in a decrease in bone density and a relative increase in adipocity. Although in vitro studies suggest the existence of an age-related lineage switch between osteogenic and adipogenic fates, stem cell and microenvironmental contributions to this process have not been elucidated in vivo. In order to study the effects of MPC and microenvironmental aging on functional engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 67 publications
4
82
0
2
Order By: Relevance
“…MSCs are characterized by plastic adherence, high growth potential, and mesenchymal immunophenotypes, as well as differentiation into mesenchymal lineages, such as osteocytes, adipocytes, chondrocytes, fibroblasts, and epithelial cells (60, 61). Aged MSCs exhibit reduced clonogenic and proliferative capacity, and differentiation potentials are skewed toward adipogenesis at the expense of osteogenesis (6264). These cells also show enlargement, telomere shortening, or p53/p21-mediated DNA damage accumulation, impaired DNA methylation or histone acetylation, and increased levels of ROS and nitric oxide (NO) (6569).…”
Section: Hematopoietic Agingmentioning
confidence: 99%
“…MSCs are characterized by plastic adherence, high growth potential, and mesenchymal immunophenotypes, as well as differentiation into mesenchymal lineages, such as osteocytes, adipocytes, chondrocytes, fibroblasts, and epithelial cells (60, 61). Aged MSCs exhibit reduced clonogenic and proliferative capacity, and differentiation potentials are skewed toward adipogenesis at the expense of osteogenesis (6264). These cells also show enlargement, telomere shortening, or p53/p21-mediated DNA damage accumulation, impaired DNA methylation or histone acetylation, and increased levels of ROS and nitric oxide (NO) (6569).…”
Section: Hematopoietic Agingmentioning
confidence: 99%
“…Both of these studies suggest that irradiation-induced BMAs are generated from recipient precursors rather than from donor cells. Interestingly, without irradiation, transplanted mesenchymal progenitor cells homed to marrow and developed into many of the BMAs observed in older recipient mice 73 .…”
Section: Functional Interactions Between Bma and Other Cells Within Tmentioning
confidence: 99%
“…A more critical functional compromise of BMMSCs in aging is impaired osteogenesis with misdirected differentiation toward adipocytes, a key process involved in the pathogenesis of osteoporosis . Notably, a recent study revealed that after transplantation into old recipient mice, the differentiation of BMMSCs shifted toward adipogenesis rather than osteogenesis irrespective of donor age, indicating that microenvironmental impacts are predominately responsible for MSC lineage switching in aging (Singh et al 2016). Further studies have shown that the age of donors also limits the regenerative capacity of MSCs in ectopic positions (Zhang et al 2012), inhibits their immunoregulatory potential in autoimmune diseases (Scruggs et al 2013), and abrogates their neurotrophic activity (Brohlin et al 2012), which might be due to an altered cytokine secretion of MSCs ( Fig.…”
Section: Characterizations Of Mscs In Agingmentioning
confidence: 99%